The Influence Of The Project-Based Learning Model On The Scientific Creativity Of Physics Education Undergraduate Students At Madura Islamic University: Pengaruh Model Pembelajaran Berbasis Proyek Terhadap Kreativitas Ilmiah Mahasiswa Pendidikan Fisika Universitas Islam Madura - Sumo, Maimon; Jatmiko, Budi; Supardi, Zainul Arifin Imam; Suprianto, Suprianto (Universitas Muhammadiyah Sidoarjo, 2024)
Scientific creativity is a skill needed in the 21st century. 21st-century skills are known as 4C skills, one of which is being creative to produce innovative work to answer the challenges of the Industrial Revolution era 5.0. The Project-based learning model is a learning model that can guide students to increase students' scientific creativity through a series of questions that direct and explore students' scientific knowledge and creativity. This research used a quasi-experimental research design with 36 students divided into control classes and experimental classes. This research aims to see how much influence the PjBL learning model has in increasing the scientific creativity of students in physics subjects in terms of the implementation of the model and the influence of the PjBL model. The instruments used to obtain data were essay test questions for pretest and posttest, and observation sheets to observe the implementation of learning in class. All test questions have been validated by experts and tried out to test the reliability of the questions, level of difficulty, and distinguishing power of the questions using the ANATES Essay Questions application. Concept mastery data (posttest) was analyzed by hypothesis testing (t-test) using the SPSS application. The results of the research show that: (1) There is a significant influence of using the Project-based learning model on students' mastery of physics concepts. A significance value of 0.031 (Sig < 0.05) was obtained at the 95% confidence level. (2) The implementation of the project-based learning model accompanied by probing prompting techniques is included in the good category